Enhancing tax education effectiveness through technology-based media and social change: a study on tax compliance among individual taxpayers - Tansen Simanullang; Hendrian Hendrian; Shine Pintor Siolemba Patiro (Jurnal Mantik, 2024)
This study focuses on the effectiveness of tax education utilizing technology-based media and the impact of social change on tax compliance among individual taxpayers. The research was conducted at various Tax Service Offices in Indonesia. The aim of this study is to analyze the influence of technology-based tax education and social change on tax compliance levels and tax revenue. The objective of this quantitative research is to examine the relationship between technology-based tax education, social change, and tax compliance levels, aiming to provide insights into improving tax compliance strategies. This study employed a mixed-methods approach, combining surveys and interviews for data collection. Quantitative data were analyzed using statistical tools, while qualitative data underwent thematic analysis to explore the nuances of taxpayer behavior in response to technology-based tax education and social change. Data collection took place from September to October 2023. The analysis revealed a significant positive correlation between technology-based tax education, social change, and tax compliance levels among individual taxpayers. The study demonstrated that effective tax education strategies utilizing technology-based media can enhance tax compliance rates. The findings suggest that utilizing technology-based media for tax education, coupled with addressing social changes, can positively impact tax compliance among individual taxpayers.